SYMBOLIQUE TITROLOGIQUE ET CONFIGURATIONS ISOTOPIQUES DANS CONVERGENCES INATTENDUES DE MATHIEU WETETO WA DJEMBA - Mutombo, Alexis KATAMBWA (IJRDO - Journal of Social Science and Humanities Research, 2022)
Under the light of the semantic interpretation, we demonstrate that the novel under analysis is articulated in an hypertheme : migration and two subthemes : the contact betwen peoples and cultures, and the social ascension. Furthermore, the semantic isotopies which cross the text are disposed in a binary opposition.In fact the special frame of life opposes the african realities to european ones, life in community opposes the cultural mixture to racism and the quality of human resources opposes the conscious diaspora to the irresponsible diaspora. From those isotopies emerge three unexpected convergences which symbolize the victory of the culturel intermixture over the extremism of love over the hatred, and of determination over despair.